Perancangan Sistem Informasi Pelacakan Keluhan Pelanggan Berbasis Customer Relationship Management PDAM Bengkulu - Mahdalena, Desi; Yulianti, Liza; Sedduantara, Sedduantara (LPPM UNIKA Santo Thomas, 2023)
This study aims to create an information system for tracking customer complaint through Customer Relationship Management in PDAM Bengkulu city to facilitate to track customer complaints submitted, see the progress of complaints whether it has not been processed, has been processed and completed in the process, and make it easy for the company to manage customer complaints and improve the relationships with customers. Data collection methods used were observation, interview and literature study. From the results of the research, the Customer Relationship Management information system in PDAM Bengkulu City can facilitate the customers to track complaints submitted, see the progress of complaints whether they have not been processed, have been processed and finished in the process, and make it easy for the company to manage customer complaints and improve relationships with customers. The results of testing the black box, 94% of customer complaint tracking information system can provide functions and benefits for the customers of PDAM Bengkulu city